Trajectories of social change in the development of Nepal’s countryside: Some sociological reflections - Luintel, Youba Raj (Unity Journal, 2020)
This paper explores dynamics in the capitalist market relations in Nepal's agricultural sector and the resultant structural social change in Mahesh Khola, a village west of the capital city, Kathmandu. I have studied a case of the Mahesh Khola valley during a couple of decades, from 1985 to 2008, to examine the expansion of agricultural markets as a mechanism to transform rural livelihoods into the market–operated capitalist set up. In this research work, I would unfold how a process of transformation of agricultural sector replicates a real development of the rural sector, resulting in social disruptions and widening social inequalities. I juxtapose such a long-term social change I discerned in Mahesh Khola with other studies of similar kind, one in Thak village, closer to Pokhara (Macfarlane, 2001) and the other along the corridor or Siddhartha Highway, from Lumbini to Pokhara (Blaikie et al., 2002). In doing so, my emphasis will be on investigating how the society-market interface evolved in the dynamics of an agrarian society.